Supervisory Behavior That Affects Worker’s Safety Behavior in Construction Project - Bayu Purnama; Anton Soekiman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
As development progresses in Indonesia, there is an increase in the number of work accidents in the Indonesian construction industry. Therefore, the researcher wants to identify the supervisory behavior of project supervisors that can significantly impact workers' safety behavior in construction projects and describe the appropriate impact path using Structural Equation Modeling (SEM). This study uses a purposive sampling method. In contrast, this study's sample is construction workers involved in construction projects that implement safety management at construction sites. The results obtained from confirmatory factor analysis and structural equation modeling indicate that there are direct and indirect impacts of supervisory behavior on worker safety behavior. Reactive and supportive actions had a direct impact on the safety behavior of workers (β = 0.036), but had no impact on the safety climate. In contrast, training and preventive actions had an indirect impact on worker safety behavior (β = 0.393), which was mediated by four safety climate factors, namely (1) worker involvement, (2) supervisory environment, (3) workmate influence and (4) competence.